Teaching Multigrade Classes in the Rural Philippines: Challenges and Opportunities - Bunglay, Lyndie Lou Pulvera; Cutab, Gerlie Dagoc (Universitas Pattimura, 2025)
This study assessed the extent of challenges and opportunities encountered by multigrade teachers in a rural elementary school in the Philippines. Using a descriptive research design, data were collected from 32 multigrade teachers across selected districts through a validated and adapted questionnaire. Results revealed that teachers experienced challenges to a moderate extent, particularly in managing diverse learners, handling increased workloads, and coping with limited instructional materials. Conversely, opportunities were reported to a high extent, especially in collaboration with stakeholders, the use of formative assessments, and the implementation of flexible teaching strategies. ANOVA results indicated no significant differences across age, teaching experience, or educational attainment, underscoring the systemic nature of multigrade challenges. The study contributes to the body of discourse on multigrade education and rural pedagogy in the Southeast Asian context by providing empirical evidence from a rural setting. It demonstrates that multigrade challenges are systemic, yet they foster teacher resilience, which in turn generates innovative practices and valuable insights to inform policies aimed at strengthening rural education.